Jordan : Request for a Stand-By Arrangement-Staff Report; Staff Supplement; Request for Modification of Performance Criteria; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Jordan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2012)
Jordan's external vulnerabilities, arising mainly from the energy sector, increased during the last decade. Aided by exceptionally large grants, fiscal policy accommodated the social impact of these shocks. Concerns about social tensions at the beginning of the year put on hold the needed fiscal consolidation. At the same time, balance of payments pressures intensified. The authorities' program is designed to correct the fiscal and external imbalances and support the exchange rate peg. Structural policies will focus on supporting growth and employment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet